Relevansi Skala Optimum Belanja Pemerintah terhadap Pertumbuhan Ekonomi dan Financial Distress Kabupaten/Kota di Provinsi Maluku - Ketut Arya Udayana; Alfie Satria Hidayat; Sani Andina Yuniati; Briliana Cahya Meilana; Chynika Salsabillah Putri (Direktorat Sistem Perbendaharaan, 2022)
This research attempts to evaluate the impact of optimum government size to economic growth and the government financial distress in districts of Maluku. The government size would intuitively drive economic growth. Especially in the eastern hemisphere of Indonesia which has lower economic activity compared to other regions. Furthermore, the bigger government size would increase the government's financial distress, since the income could not cover the mandatory spending and long term liabilities. The evidence of this research shows that the government size does not significantly impact both the per capita regional GDP and financial distress of the districts in Maluku. However, the level of private sector investment is significant in forming the per capita regional GDP and the level of liabilities would affect the level of government financial distress. The results also demonstrate the importance of government expenditure composition, especially mandatory spending, that may be considered as the significant factors that impact overall economy and the local government financial condition.